2019
DOI: 10.1093/mnras/stz1232
|View full text |Cite
|
Sign up to set email alerts
|

Separating extended disc features from the protoplanet in PDS 70 using VLT/SINFONI

Abstract: Transition discs are prime targets to look for protoplanets and study planet-disc interactions. We present VLT/SINFONI observations of PDS 70, a transition disc with a recently claimed embedded protoplanet. We take advantage of the angular and spectral diversity present in our data for an optimal PSF modeling and subtraction using principal component analysis (PCA). We report the redetection of PDS 70 b, both the front and far side of the outer disc edge, and the detection of several extended features in the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 83 publications
7
56
2
Order By: Relevance
“…Our mass and radius ranges for PDS 70 b are also consistent with the atmospheric 'planet alone' models of Christiaens et al (2019b) as fitted to the observed K-band spectrum; by comparison, their 'planet + CPD' model yields a more massive best fit of 10 M J . In addition, our inferred accretion rate agrees with the upper limit estimated from the non-detection of Brγ emission by Christiaens et al (2019a). Earlier we saw that the high luminosity of the companion to MWC 758 could be explained by post-runaway accretion in a viscous disk but not in an inviscid one.…”
Section: Interpreting Observationssupporting
confidence: 89%
“…Our mass and radius ranges for PDS 70 b are also consistent with the atmospheric 'planet alone' models of Christiaens et al (2019b) as fitted to the observed K-band spectrum; by comparison, their 'planet + CPD' model yields a more massive best fit of 10 M J . In addition, our inferred accretion rate agrees with the upper limit estimated from the non-detection of Brγ emission by Christiaens et al (2019a). Earlier we saw that the high luminosity of the companion to MWC 758 could be explained by post-runaway accretion in a viscous disk but not in an inviscid one.…”
Section: Interpreting Observationssupporting
confidence: 89%
“…Mass accretion rates have been estimated for both PDS 70b and c. Wagner et al (2018) detection of Hα emission at the location of PDS 70b led them to conclude that the planet is actively accreting mass from its disk. They used the Hα flux to estimate a mass accretion rate onto the planet ofṀ∼ 10 −8 M Jup yr −1 , which is consistent with the upper limit estimated by Christiaens et al (2019) from the lack of detection in Brγ. Haffert et al (2019) also inferred values of the mass accretion rate, but they used the width at the 10% height (W 10 ) of the Hα line estimates for PDS 70b and c, applying the correlation from Natta et al (2004).…”
Section: Introductionsupporting
confidence: 63%
“…It is known that aggressive ADI processing of observations can cause extended emission, such as spiral arms, to appear as point sources (e.g. Christiaens et al 2019). Comparison between the bottom panels of Figure 2 shows indeed a spiral feature in the simulation at the location of 'b' in the observation.…”
Section: Companion Candidatesmentioning
confidence: 86%
“…While our procedure does not deal with speckle noise, our goal is to reproduce the geometric and flux biases induced by ADI on extended disc signals (e.g. Milli et al 2012;Christiaens et al 2019).…”
Section: Post-processing Of Infrared Imagesmentioning
confidence: 99%